Variability of extracellular vesicle release during storage of red blood cell concentrates is associated with differential membrane alterations, including loss of cholesterol-enriched domains - Ghodsi, Marine; Cloos, Anne-Sophie; Mozaheb, Negar; Van Der Smissen, Patrick; Henriet, Patrick; Pierreux, Christophe E.; Cellier, Nicolas; Mingeot-Leclercq, Marie-Paule; Najdovski, Tomé; Tyteca, Donatienne (Frontiers in Physiology, 2023)
Transfusion of red blood cell concentrates (RCCs) is the most common medical procedure practiced worldwide to treat anaemia. However, RCC storage is associated with development of red blood cell (RBC) storage lesions, including the release of extracellular vesicles (EVs). These EVs affect in vivo viability and functionality of transfused RBCs and appear responsible for adverse post-transfusional complications. However, the mechanism behind EV biogenesis and release is not fully understood. We here addressed this issue by comparing the kinetics and extents of EV release as well as RBC metabolic, oxidative and membrane alterations upon storage in 38 RCCs. We showed that EV abundance increased exponentially during storage. The 38 RCCs contained on average 7x1012 EVs at 6 weeks (w) but displayed a high (~40-fold) variability. These RCCs were subsequently classified into 3 cohorts based on their vesiculation rate. The variability in EV release was not associated with a differential ATP content or with increased oxidative stress (in forms of reactive oxygen species and methemoglobin) but rather with RBC membrane modifications, i.e. cytoskeleton membrane occupancy, lateral heterogeneity in lipid domains and transversal asymmetry. Indeed, no obvious change was noticed in the low vesiculation group until 6w. In contrast, both the medium and the high vesiculation groups exhibited a decrease in spectrin membrane occupancy between 3 and 6w and an increase of sphingomyelin-enriched domain abundance from 5w and of phosphatidylserine surface exposure from 7w. Moreover, the high vesiculation group showed the highest cholesterol-enriched domain decrease from the RBC surface between 3 and 6w and the strongest EV enrichment in cholesterol, suggesting that these domains could represent a starting point for EV release. Altogether, our data reveal for the first time that the differential extent of EV release in RCCs did not simply result from RCC preparation method, storage conditions or technical EV-related issues but is linked to RBC membrane alterations. Additionally, our study paves the way for targeting cholesterol-enriched domains to limit EV generation in RCCs.